Are ICT Displacing Workers? Evidence from Seven European Countries - Smaranda Pantea; Federico Biagi; Anna Sabadash (European Commission, Joint Research Centre (JRC), 2014)
This paper examines whether ICT substitute labour and reduce the demand for labour. We used firm-level comparable data separately for firms in manufacturing, services and ICT-producing sectors from seven European countries. We adopted a common methodology and applied it to a unique dataset provided by the ESSLait Project on Linking Microdata. We controlled for unobservable time-invariant firm-specific effects and we found no evidence of a negative relationship between intensity of ICT use and employment growth. We read this as an indication that ICT use is not reducing employment among ICT using firms.
Keywords: J23; J24; O33; L86; 330; Labour Demand; Technological Change; ICT